Book Publishers Cited in Science Dissertations: Are Commercial Publishers Worth the Hype?. Issue 1 (2nd January 2017) - Franks, Tina P.; Dotson, Daniel S.
ABSTRACT: Library funds are frequently spent to purchase books released by commercial publishers. This case study seeks to identify publisher types most often cited by PhD students. Almost 4, 300 citations from 487 science dissertations published at The Ohio State University between 2003 and 2012 were examined to determine the types of book publishers cited. Results revealed that the commercial book publishers continue to rank the highest among researchers; however, some disciplines may reference or cite other types of book publisher categories. When comparing overall rankings, commercial book publishers have clearly shown a dominance during the 10-year review period.